Media Cetak di Era Digital : (Analisis Kekuatan Harian Pagi Jawa Pos Radar Banyuwangi) - Agus Baihaqi (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, IAI Al-Qodiri Jember, 2023)
ABSTRAK Print media is facing some difficult times. The development of information technology that gave rise to the internet has given birth to online media. This online media can present the news that is fast, practical, and efficient. Until finally shifting to conventional print media. In the last of 10 years, dozens of local, national, and international print media have chosen to close. Some have stopped publishing, but some follow the trend by switching to online. Jawa Pos Radar Banyuwangi, a local newspaper that is inserted into Jawa Pos, is one of the print media that can survive in online media. This research was conducted to find out the strengths possessed, and the strategies carried out so that they can survive. The method used in this research is descriptive qualitative research, extracting data using interviews and observations. Based on the research results, it is known that Jawa Pos Radar Banyuwangi can survive the onslaught of online media, by converging. Creating new products in the form of online media and YouTube. In addition, it also makes social media Instagram, Twitter, and Facebook. This printing media also strengthens its character by maintaining data accuracy, appearance, and infographics.